TEACHERS’ ROLE IN EMBEDDING DISCIPLINE CHARACTERS TO GRADE IV STUDENTS THROUGH LEARNING ACTIVITIES AT SDN KARAWACI BARU 6 - Rita Novia Elviana; Hosnan; Suparno (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2021)
Discipline is one of the keys to success. Discipline is not only owned by students; but all jobs also must own discipline to show that the values of obedience and order are in accordance with the applicable norms and rules. Teachers also play an important role to overcome the lack of discipline among students since students spend a lot of time at school with teachers, especially class teachers. This study aimed to determine how teachers embedded discipline to grade IV students through learning activities. The method used in this study was descriptive qualitative method. The data were collected through interview, observation, and documentation techniques. The results of this study indicated that teachers of SDN Karawaci Baru 6 were able to embed the discipline character to grade IV students and knew how to achieve subject characteristics through learning activities.